Zinc oxide hollow spheres decorated with cerium dioxide. The role of morphology in the photoactivity of semiconducting oxides. (11th January 2022) - Cerrato, Erik; Chiesa, Mario; Giamello, Elio; Livraghi, Stefano; Salvadori, Enrico; Paganini, Maria Cristina
Abstract: The photochemical activity of the recently proposed CeO2 –ZnO photocatalytic material active under visible light has been improved by means of significant modifications of its morphology. A polymeric templating agent (Pluronic) has been used in the synthesis obtaining a particle morphology based on hollow spheres that is better defined in the case of high template concentration. The charge separation ability and the light-induced surface electron transfer under irradiation with visible polychromatic light in various ranges of wavelengths has been investigated by electron paramagnetic resonance. The reactivity of the photogenerated holes has been monitored by the spin trapping technique in the presence of DMPO. The hollow spheres morphology achieved through the synthesis here reported leads to systems with a higher photoactivity under visible irradiation than the same system displaying the classic platelets morphology. A parallel increase of the photocatalytic activity of this novel system in pollution remediation reactions is therefore predictable.